Development of a measurement technique for detailed flow characterization in fuel bundles - Nalin, Oscar Cesar Augusto; Marcel, Christian Pablo; Lazo, Pablo Miguel; Masson, Viviana Patricia (Elsevier Science Sa, 2018)
Fil: Nalin, Oscar Cesar Augusto. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina